The Effect of Inotropes and Vasopressors on Mortality: A Meta-analysis of Randomized Clinical Trials. Issue 5 (October 2016) - Belletti, A.; Castro, M. L.; Silvetti, S.; Greco, T.; Biondi-Zoccai, G.; Pasin, L.; Zangrillo, A.; Landoni, G.
Abstract : (Abstracted from Br J Anaesth, 115:656–675, 2015) Some studies have suggested that the use of inotropes to improve hemodynamic function and restore adequate organ perfusion in critically ill patients is linked to increased mortality. Researchers examined 20 years' worth of randomized trials (using studies published after January 1994) to investigate the effect of inotropes and vasopressors on mortality.